2021
DOI: 10.3390/land10060572
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing Determinants to Smallholders’ Market Orientation and Marketing Arrangements: Building on a Case of Dairy Farming in Rural Kenya

Abstract: Smallholder commercialization is central to international development policy and practice. As a result, several arrangements to foster market linkages are being implemented. Especially popular are farmers’ organizations, which are believed to be owned, controlled, and financed by smallholders. As such, their design is considered inclusive given every household in a community is theoretically allowed to become a member, and the governance and management structure encourage participatory decision-making. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Among the primary reasons for this critical disparity is growing (global and local) social and economic inequality ( Dixon et al, 2007 ). Elsewhere, recent studies on inclusive agribusiness, the currently popular and dominant approach for improving smallholder livelihoods, food and nutrition security therein, show that not every farmer gets to participate, while those that do and manage to obtain better income it does not necessarily lead to improved food and nutrition security ( Wangu et al, 2020 ; Wangu et al, 2021 ; Gebru et al, 2019 ). On a different note, agriculture is associated with adverse environmental implications that undermine food production ( Steffen et al, 2015 ).…”
Section: A Sustainable and Resilient Food Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the primary reasons for this critical disparity is growing (global and local) social and economic inequality ( Dixon et al, 2007 ). Elsewhere, recent studies on inclusive agribusiness, the currently popular and dominant approach for improving smallholder livelihoods, food and nutrition security therein, show that not every farmer gets to participate, while those that do and manage to obtain better income it does not necessarily lead to improved food and nutrition security ( Wangu et al, 2020 ; Wangu et al, 2021 ; Gebru et al, 2019 ). On a different note, agriculture is associated with adverse environmental implications that undermine food production ( Steffen et al, 2015 ).…”
Section: A Sustainable and Resilient Food Systemmentioning
confidence: 99%
“…Indeed, studies have shown that in the same community there is a variation in smallholder households' socio-economic attributes with some households being relatively resource rich whilst others are significantly deprived. These conditions dictate who is able to participate and benefit from available socio-economic opportunities ( Wangu et al, 2020 ; Wangu et al, 2021 ; Johnson et al, 2016 ). Consequently, a variation in socio-economic outcomes, such as meeting their household food security, is to be expected.…”
Section: Understanding Gender Duality In Food Systems and Food Securi...mentioning
confidence: 99%
See 2 more Smart Citations
“…The concerns for people and profit are related to the effects of climate change on livestock keepers in predominantly rainfed agricultural systems. In Kenya, dairy cattle populations constitute 25% of the total livestock population (Mbae et al, 2020), and are kept by an estimated 1.3 million households (Wangu et al, 2021). Smallholder producers, owning one to three dairy cows account for about 80% of the milk produced in Kenya, making dairy cattle an important livelihood asset for many rural residents (Makoni et al, 2013).…”
Section: The Societal Challenge: Achieving Triple Wins For Livestock ...mentioning
confidence: 99%